Effects of exogenous lactoferrin on phenotypic profile and invasiveness of human prostate cancer cells (DU145 and LNCaP) in vitro - Zadvornyi, T.V.; Lukianova, N.Y.; Borikun, T.V.; Chekhun, V.F. (Experimental Oncology, 2018)
Aim: To investigate the biological effects of exogenous lactoferrin (LF) on phenotypic profile and invasiveness of human prostate cancer (PC) cells in vitro. Materials and Methods: Human PC cell lines (LNCaP, DU-145) were cultured with an exogenous LF at a dose corresponding to IC30. The expression levels of steroid hormone receptors (androgen receptor, estrogen receptor, progesterone receptor), Her2/neu, Ki-67, E- and N-cadherin, were monitored by immunohistochemical analysis. The levels of miRNAs were assessed using q-PCR. The invasive activity of the cells was examined in a standard invasion test. Results: Exogenous LF reduced expression of steroid hormone receptors (ERα and PR) and Ki-67 in both PC cell lines. The expression of E-cadherin increased significantly in LF-treated DU-145 cells. Also, we established the decrease in invasive activity upon LF treatment by 40% and 30% in DU-145 and LNCaP cells, respectively. In DU-145 cells, incubation with exogenous LF resulted in an increase in the expression of oncosuppressive (miR-133a and miR-200b) miRNAs. Conclusions: Exogenous LF causes the changes in phenotypic characteristics of PC cells and levels of oncogenic and oncosuppressive miRNAs involved in the regulation of key cellular processes. Key Words: prostate cancer, exogenous lactoferrin, DU145, LNCaP, miRNA.